PENGARUH LITERASI KEUANGAN, PENDAPATAN ORANG TUA DAN GAYA KOGNITIF TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA UNIVERSITAS WIRABHAKTI MAKASSAR PADA MASA PANDEMI COVID-19 - Andanika, Andanika (Paser Institute Of Accounting and Finance, 2023)
This research aims to determine the influence of financial literacy variables, parental income, cognitive style on financial management behavior. The population in this study were students majoring in management at Wirabhakti University, Makassar. The sample in this research consisted of 150 respondents, using a probability sampling method. Data collection was carried out through distributing questionnaires. The analysis technique used is SPSS statistical analysis. The results of this research show that: (1) Financial literacy has no significant effect on students' financial management behavior during the Covid-19 pandemic, (2) Parental income has a significant effect on students' financial management behavior during the Covid-19 pandemic, (3) Cognitive style has a significant effect on student financial management behavior during the Covid-19 pandemic.